ANALYSIS AND PARAMETERS OPTIMIZATION OF TOOTH PLATE OF IRON ROUGHNECK CLAMPING PLIERS - PEI JunFeng; SONG ChuanZhi; LIU ZhiGang; CHEN Jie; SHEN Hui; MIAO HongJian (Jixie qiangdu)
Based on the ANSYS Workbench finite element software, the ultimate static working state of the dental plate of clamping pliers when drilling the drill string is analyzed elastoadically. The stress of the contact between the dental tooth and the drill pipe was analyzed by linearization principle, and the classification was identified and evaluated. And then the key parameters of tooth plate as the object of study, through the orthogonal experiment results of the poor analysis, combined with the actual processing capacity to determine the final optimization program. Finally, the contact stress between the dental plate and the drill pipe was measured by the pressure film, and the rationality of the optimization scheme was verified, and the pressure applied is linearly related to the maximum stress of the tooth plate.The test method provides a new way for the same type of equipment. It is of great engineering significance to ensure the safe, reliable and effective operation.